AN ANALYSIS OF THE EFFECT OF INSTITUTIONAL DISTANCE ON THE LEVEL OF CONTROL OF MULTINATIONALS IN THE INDONESIAN MEDIUM-HIGH AND HIGH TECHNOLOGY INDUSTRY - Pramuditya, Rio (PEOPLE: International Journal of Social Sciences, 2024)
Multinational corporations (MNCs) significantly contribute to globalizing research and development, particularly in emerging economies like Indonesia. As Indonesia aims to achieve the "Making Indonesia 4.0" vision, attracting foreign investment to bolster its medium-high and high technology industry becomes crucial. This study conducts an exploration within institutional theory concerning the influence of ’distance’ measures on the level of control exerted by MNCs in a host country. Focusing on Indonesia’s medium-high and high technology industry, the research investigates the relationships between formal and informal institutional distances and MNCs’ strategic control decisions. Statistical analyses support the hypotheses, affirming the significance of both formal and informal institutional distance in shaping MNCs’ inclination toward majority stake deals in the targeted industry. The findings contribute to a nuanced understanding of MNCs’ strategic decision-making in an industry specific context. Which necessitates MNCs to balance managing partnerships to reduce strategic control in a formally distant host country, while at the same time maintaining a strong grip on technology-intensive activities to mitigate risks tied to reduce interdependence in an informally distant host country.